A new perspective on the evolution and diversity of the genus Amdoparvovirus (family Parvoviridae) through genetic characterization, structural homology modeling, and phylogenetics. Issue 1 (17th June 2022) - Canuti, Marta; Pénzes, Judit J; Lang, Andrew S
Abstract: Amdoparvoviruses (genus Amdoparvovirus, family Parvoviridae ) are primarily viruses of carnivorans, but recent studies have indicated that their host range might also extend to rodents and chiropterans. While their classification is based on the full sequence of the major nonstructural protein (NS1), several studies investigating amdoparvoviral diversity have been focused on partial sequences, leading to difficulties in accurately determining species demarcations and leaving several viruses unclassified. In this study, while reporting the complete genomic sequence of a novel amdoparvovirus identified in an American mink (British Columbia amdoparvovirus, BCAV), we studied the phylogenetic relationships of all amdoparvovirus-related sequences and provide a comprehensive reevaluation of their diversity and evolution. After excluding recombinant sequences, phylogenetic and pairwise sequence identity analyses allowed us to define fourteen different viruses, including the five currently classified species, BCAV, and four additional viruses that fulfill the International Committee on Taxonomy of Viruses criteria to be classified as species. We show that the group of viruses historically known as Aleutian mink disease virus (species Carnivore amdoparvovirus 1 ) should be considered as a cluster of at least four separate viral species that have been co-circulating in mink farms, facilitating the occurrence of inter-species recombination. Genome organization, splicing donor and acceptor sites, and protein sequence motifs were surprisingly conserved within the genus. The sequence of the major capsid protein virus protein 2 (VP2) was significantly more conserved between and within species compared to NS1, a phenomenon possibly linked to antibody-dependent enhancement (ADE). Homology models suggest a remarkably high degree of conservation of the spikes located near the icosahedral threefold axis of the capsid, comprising the surface region associated with ADE. A surprisingly high number of divergent amino acid positions were found in the luminal threefold and twofold axes of the capsid, regions of hitherto unknown function. We emphasize the importance of complete genome analyses and, given the marked phylogenetic inconsistencies across the genome, advise to obtain the complete coding sequences of divergent strains. Further studies on amdoparvovirus biology and structure as well as epidemiological and virus discovery investigations are required to better characterize the ecology and evolution of this important group of viruses.